Complicated traumatic pulmonary pseudocyst: a case report - Ali Hossein Samadi Takaldani; Rona Jannati; Amirpasha Mansour (Trauma Case Reports, 2025)
A traumatic pulmonary pseudocyst (TPP) is an uncommon lung lesion that can occur due to blunt chest trauma. This condition is usually harmless and doesn't require medical treatment, but in rare cases, it is complicated by rupture of the lesion and hemothorax. We present the case of a 43-year-old man who fell from a height and suffered chest trauma. Imaging revealed a mass-like lesion and hemothorax, but after ruling out other diagnoses, he was diagnosed with complicated traumatic pulmonary pseudocyst. Over six months, the mass-like lesion shrank and disappeared entirely without any remaining scars. Proper diagnosis and differentiation from other lung lesions are essential in cases of TPP. With conservative management and regular follow-up, the prognosis is generally reasonable.